2013
DOI: 10.1371/journal.pone.0063549
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Donor Supplementation Blocks the Adverse Effects of Maternal High Fat Diet on Offspring Physiology

Abstract: Maternal consumption of a high fat diet during pregnancy increases the offspring risk for obesity. Using a mouse model, we have previously shown that maternal consumption of a high fat (60%) diet leads to global and gene specific decreases in DNA methylation in the brain of the offspring. The present experiments were designed to attempt to reverse this DNA hypomethylation through supplementation of the maternal diet with methyl donors, and to determine whether methyl donor supplementation could block or attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 50 publications
6
88
2
2
Order By: Relevance
“…There is good evidence from animal models of undernutrition during foetal life that maternal diet can alter the epigenome, particularly DNA methylation, and this may establish changes in gene expression that permanently modify tissue structure or reset the responses to dietary and age-related challenges that occur later in life (Sinclair et al 2007;Lillycrop et al 2007;Bogdarina et al 2010). Exposure to high-fat diets has been shown to alter DNA methylation and histone marks in rodents, non-human primates and primates, with the brain being particularly sensitive to dietary influences (Seki et al 2012;Carlin et al 2013;Langie et al 2013;Jacobsen et al 2012). The theory that epigenetic marks are solely vulnerable to nutritional programming in foetal life is now discounted as the epigenome responds to dietary cues at all life stages.…”
Section: Introductionmentioning
confidence: 99%
“…There is good evidence from animal models of undernutrition during foetal life that maternal diet can alter the epigenome, particularly DNA methylation, and this may establish changes in gene expression that permanently modify tissue structure or reset the responses to dietary and age-related challenges that occur later in life (Sinclair et al 2007;Lillycrop et al 2007;Bogdarina et al 2010). Exposure to high-fat diets has been shown to alter DNA methylation and histone marks in rodents, non-human primates and primates, with the brain being particularly sensitive to dietary influences (Seki et al 2012;Carlin et al 2013;Langie et al 2013;Jacobsen et al 2012). The theory that epigenetic marks are solely vulnerable to nutritional programming in foetal life is now discounted as the epigenome responds to dietary cues at all life stages.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a maternal high-fat diet supplemented with methyl donors (choline, betaine, folic acid, vitamin B 12 , L-methionine, and zinc) prevented high-fat-dietinduced weight gain, fat preference, and global hypomethylation in higher-order reward regions in mice. 118 Only two studies have assessed the potential lasting effects of maternal vitamin excess during pregnancy on the mother. In a preliminary study, 119 dams were fed an HV or high-folic-acid diet during pregnancy and then an RV diet during the postweaning period.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…We have found that the group having received HFD with a supplementation of methyl donors (Folic acid, Cholin, betain, L-methionin and Vi-Open Journal of Endocrine and Metabolic Diseases tamin B12) had an improved behavior in EPM and FST. It has been clearly shown that maternal diet with supplementation in methyl donor changes gene expression in central nervous system and global DNA hypomethylation in prefrontal cortex [41]. Epigenetic regulation through DNA methylation or histone acetylation is essential factors in the control of psychiatric disorders such as depression and anxiety [42] [43].…”
Section: Discussionmentioning
confidence: 99%